(untitled) (Global Journal of Human-Social Science, 2014)
The main thesis in this study is anchored on the declaration of Omu (1978, p. 248) and Dare (1997, p. 537) on the performance of post-independence press in Nigeria. While Omu states that the post-independence press in Nigeria "provided a remarkable example of overzealous and irresponsible partisanship", Dare, quoting one of the architects of modern Nigeria, Anthony Enahoro equally states that "the Nigerian press lacked men of stature as well as the vision to recognize danger and the courage to oppose wrong". There is no doubt, election periods are usually exciting moments in every democratic society. It is a period for the showing of strength by political parties and candidates from constituency to constituency. It is also a period when the electorate shows appreciation and support to candidates and political parties who had fulfilled their electoral promises. During this period, proprietors of newspapers daily smile to the banks as the sale of newspapers pick up just as advert patronages also increase.